Clinical and biological significance of RAD51 expression in breast cancer: a key DNA damage response protein - Alshareeda, Alaa; Negm, Ola H.; Aleskandarany, Mohammed A.; Green, Andrew R.; Nolan, Christopher; Tighe, Patrick J.; Madhusudan, Srinivasan; Ellis, Ian O.; Rakha, Emad (Springer, 2016)
Impaired DNA damage response (DDR) may play a fundamental role in the pathogenesis of breast cancer (BC). RAD51 is a key player in DNA double-strand break repair. In this study, we aimed to assess the biological and clinical significance of RAD51 expression with relevance to different molecular classes of BC and patients’ outcome. The expression of RAD51 was assessed immunohistochemically in a well-characterised annotated series (n = 1184) of early-stage invasive BC with long-term follow-up. A subset of cases of BC from patients with known BRCA1 germline mutations was included as a control group. The results were correlated with clinicopathological and molecular parameters and patients’ outcome. RAD51 protein expression level was also assayed in a panel of cell lines using reverse phase protein array (RPPA). RAD51 was expressed in the nuclei (N) and cytoplasm (C) of malignant cells. Subcellular colocalisation phenotypes of RAD51 were significantly associated with clinicopathological features and patient outcome. Cytoplasmic expression (RAD51C+) and lack of nuclear expression (RAD51 N-) were associated with features of aggressive behaviour, including larger tumour size, high grade, lymph nodal metastasis, basal-like, and triple-negative phenotypes, together with aberrant expression of key DDR biomarkers including BRCA1. All BRCA1-mutated tumours had RAD51C+/N- phenotype. RPPA confirmed IHC results and showed differential expression of RAD51 in cell lines based on ER expression and BRCA1 status. RAD51 N+ and RAD51C+ tumours were associated with longer and shorter breast cancer-specific survival (BCSS), respectively. The RAD51 N+ was an independent predictor of longer BCSS (P<0.0001). Lack of RAD51 nuclear expression is associated with poor prognostic parameters and shorter survival in invasive BC patients. The significant associations between RAD51 subcellular localisation and clinicopathological features, molecular subtype and patients’ outcome suggest that the trafficking of DDR proteins between the nucleus and cytoplasm might play a role in the development and progression of BC.